Online Shopping Behavior: An In-depth Study on Motivating and Restraining Factors (Global Journal of Management and Business Research, 2018)
Albeit Bangladesh has a bright future in e-commerce; the number of online shoppers is negligible comparing to the number of internet users. Fostering this in mind this study attempts to explore the dominant factors behind this along with demographic factors of the online shoppers. Descriptive statistics have been carried out using SPSS software. Primary data were collected using a structured questionnaire. Researcher procured secondary data from the published papers, books journals and websites. The study found that perceived advantages of online shopping motivate consumers to shop through the internet, whereas, risks, disadvantages and security issues create an obstacle in the mind of consumers. Moreover male consumers are more prone to online shopping than female. Male consumers mostly purchase books and magazines comparing to females who commonly shop apparels and accessories from online marketers. Researchers provide some recommendations for the Bangladeshi e-marketers on which strategies and techniques to practice to increase the number of internet shoppers.
Keywords: online shopping; e-commerce; click-n-mortar; brick-n-mortar; cognitive dissonance; perceived advantage; perceived disadvantage; demographic factor